Encouraging Students’ Interest in Learning English Through Annual Program, “The Election of Miss and Mister Smanti’ in SMA Negeri 3 Merauke - Winarsih, Sri (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2016)
SMA Negeri 3 Merauke used to be a pioneer ofInternational Standard School which is often called RSBI. It wasthe only senior high school in Merauke with that status at the time.Since bearing a predicate as the pioneer of international standardschool, SMA Negeri 3 Merauke has been activating manyprograms which aim at improving English ability either forstudents or for teachers. One most attractive activity for thestudents is the annual program, ‘the election of Miss and MisterSMANTI’. The program that imitated the famous program intelevision, Miss Indonesia, got surprising responses from thestudents, the students’ parents, even the school committees. It isrecognized as the prestigious one since the election demands thecontestants’ English ability. More evidence of the success is thatthe program even led the other schools in Merauke to imitate thesame program in their annual school programs. This paper aims toshow how the program encourages students’ interest in learningEnglish. Through the observation, it can be known how theprogram runs and works. The series of the program concern withencouraging students’ interest in learning English include; 1) preactivity session; quarantine, promotion, and oration, 2) mainsession; performance, 3) following session; the role of the elected‘Miss and Mister SMANTI among their schoolmates.